Changing Income Inequality and Panel Income Changes - Robert Duval Hernández; Gary S. Fields; George H. Jakubson (Institute for the Study of Labor (IZA), 2015)
When economic growth (or economic decline) takes place, who benefits and who is hurt how much? The more traditional way of answering this question is to compare two or more comparable cross sections and gauge changing income inequality among countries or individuals. A newer way is to utilize data on a panel of countries or a panel of people and assess the pattern of panel income changes. How do these two approaches relate to one another? This paper shows, first, that it is possible to have all four combinations - rising or falling inequality and divergent or convergent panel income changes, and second, under what conditions, for various measures of rising/falling inequality and various measures of divergent/convergent income changes, each of the four possible combinations can arise.
Keywords: J31; D63; 330; income inequality; economic mobility